Faktor-Faktor yang Mempengaruhi Kepuasan Kerja pada Pekerja Lepas di DKI Jakarta - Kosasih, Julie; M. Tony Nawawi (Jurnal Riset Manajemen dan Akuntansi, 2026)
In the modern work industry, job satisfaction serves as an important fundamental for worker’s productivity and long-term career sustainability, including within the freelance sector. This study aims to determine the factors that influence job satisfaction among freelancers in DKI Jakarta, with work motivation and organizational commitment as the main variables examined. The research utilized primary data collected through an online survey distributed to 236 freelancers residing mainly in South Jakarta. The relationships between variables were analyzed using the Structural Equation Modeling (SEM) approach with the assistance of SmartPLS version 4.1. The results demonstrate that work motivation and organizational commitment have a positive and significant effect on job satisfaction among freelancers in DKI Jakarta. Based on these findings, freelance service platforms are encouraged to improve the quality of support by developing user-friendly features and ensuring responsive communication. Freelancers are also advised to strengthen their identity and professionalism, while clients are recommended to offer clear guidance and maintain open discussion to create more effective working relationships.